Grid integration techniques on wind power plants - Wong, Jing Jing. (2009)
The purpose of this project was to research on the current grid integration techniques of synchronous generator based wind turbine and develop an efficient converter topology to achieve a wide range of desirable output voltages. The scope of the project included testing the functionality and controlling the switching state of the ZSI to achieve the maximum output power. Establishment of AC voltages with a standard value compatible to grid and derivation of the optimum reference speed from wind speed were not executed. Conventional pulse-width modulation (PWM) strategy was modified to give ZSI the boost effect while controller design was based on space-vector PWM (SVPWM) technique that only needed to sense the output voltages.